The Great Recession and Social Exclusion: Homeless People in the City of Madrid - Iria Noa de la Fuente-Roldán; Esteban Sánchez-Moreno (Social Work and Society, 2022)
This article aims to analyse the impact of the Great Recession that arrived in Spain in 2008 in terms of how it has intensified and transformed social inequalities in general, and homelessness in particular. In this regard, the present article examines the social change processes in the Spanish labour market, welfare system and housing market in order to analyse their effect in transforming the life pathways that have led to homelessness in the city of Madrid (Spain). A qualitative methodology was used in the form of a biographical approach involving 10 life stories from the homeless population of Madrid. The main conclusion of the study is that the socio-structural transformations that have occurred in the Spanish context are having an increased impact on the incidence and transformation of the homeless realities.